Refugees and Covid-19: The Great Opportunity to Implement the Global Compact on Refugees - Atik Krustiyati; Yaries Mahardika Putro (Yuridika, 2022)
The Coronavirus pandemic affected several sectors including the policies of national governments and the international community. Besides cleanliness and health policies (e.g., washing hands and wearing masks), the primary policy adopted in numerous countries was the human mobility restriction. Border posts, airports, and ports are closed to limit people’s mobility, eliminating the opportunity for individuals to leave their nation because of war or unstable situations to seek a better life. Refugees are the ones who are most affected by the spread of this Coronavirus, as each nation prioritises its own national interests and its own inhabitants. The Global Compact on Refugees can be properly implemented to help refugees overcome the difficulties they face in the middle of the Covid-19 pandemic. The core objective of the Global Compact on Refugees is to ease the pressures on host countries and its equitable responsibility-sharing provisions should be optimised for implementation. This study is based on normative legal research; therefore, this article will examine the role of the Global Compact on Refugees during the height of COVID-19. Even though the Global Compact on Refugees is merely a non-legally binding instrument, the pandemic could be used as momentum for states to share the burden and responsibility of caring for the refugees in their states.